Problem Solving Ability Of Preschool Principals - Kamtini; Rosnelli; Wildansyah Lubis (JURNAL BUNGA RAMPAI USIA EMAS, 2025)
The principal's leadership is an important factor in improving the quality of education and learning in schools. This research aims to describe the problem solving abilities of kindergarten school principals in responding to problems that arise in school situations. The research involved 20 school principals in the city of Medan. The findings from this research are that in resolving and overcoming problems that occur in schools, school principals tend to use principles in planning things to do with the teachers and teaching staff at the school.